Controls on dissolved organic matter (DOM) degradation in a headwater stream: the influence of photochemical and hydrological conditions in determining light-limitation or substrate-limitation of photo-degradation - R. M. Cory; K. H. Harrold; B.T. Neilson; G. W. Kling (Biogeosciences, 2015)
We investigated how absorption of sunlight by chromophoric dissolved organic matter (CDOM) controls the degradation and export of DOM from Imnavait Creek, a beaded stream in the Alaskan Arctic. We measured concentrations of dissolved organic carbon (DOC), as well as concentrations and characteristics of CDOM and fluorescent dissolved organic matter (FDOM), during ice-free periods of 2011–2012 in the pools of Imnavait Creek and in soil waters draining to the creek. Spatial and temporal patterns in CDOM and FDOM in Imnavait Creek were analyzed in conjunction with measures of DOM degradation by sunlight and bacteria and assessments of hydrologic residence times and in situ UV exposure. CDOM was the dominant light attenuating constituent in the UV and visible portion of the solar spectrum, with high attenuation coefficients ranging from 86 ± 12 m−1 at 305 nm to 3 ± 1 m−1 in the photosynthetically active region (PAR). High rates of light absorption and thus light attenuation by CDOM contributed to thermal stratification in the majority of pools in Imnavait Creek under low-flow conditions. In turn, thermal stratification increased the residence time of water and DOM, and resulted in a separation of water masses distinguished by contrasting UV exposure (i.e., UV attenuation by CDOM with depth resulted in bottom waters receiving less UV than surface waters). When the pools in Imnavait Creek were stratified, DOM in the pool bottom water closely resembled soil water DOM in character, while the concentration and character of DOM in surface water was reproduced by experimental photo-degradation of bottom water. These results, in combination with water column rates of DOM degradation by sunlight and bacteria, suggest that photo-degradation is the dominant process controlling DOM fate and export in Imnavait Creek. A conceptual model is presented showing how CDOM amount and lability interact with incident UV light and water residence time to determine whether photo-degradation is "light-limited" or "substrate-limited". We suggest that degradation of DOM in CDOM-rich streams or ponds similar to Imnavait is typically light-limited under most flow conditions. Thus, export of DOM from this stream will be less under conditions that increase the light available for DOM photo-degradation (i.e., low flows, sunny days).